Iron cycling during the decline of a South Georgia diatom bloom. (April 2023) - Ainsworth, Joanna; Poulton, Alex J.; Lohan, Maeve C.; Stinchcombe, Mark C.; Lough, Alastair J.M.; Moore, C. Mark
Abstract: The Southern Ocean is the largest high nutrient low chlorophyll (HNLC) oceanic region, where iron limits phytoplankton growth and productivity and ultimately influences the Biological Carbon Pump (BCP). Natural exceptions to the HNLC regime occur where island wakes cause iron to be mixed into surface waters from sediments, enabling large, prolonged phytoplankton blooms and increased carbon drawdown. Interactions between iron and phytoplankton are reciprocal in blooms: with plankton regulating the (re)cycling of iron through cellular uptake and remineralisation. The depth of iron remineralisation then influences either re-supply to the surface mixed layer biota or sequestration into deeper waters. Water column trace metal observations and shipboard experiments, using bioassays and radioisotope ( 55 Fe, 32 Si, 14 C) cycling, were undertaken to investigate surface mixed layer phytoplankton iron limitation, iron uptake, and mesopelagic iron remineralisation relative to carbon and silica within the November 2017 bloom downstream of South Georgia. Surface phytoplankton residing in the iron depleted mixed layer were iron limited throughout the four-week sampling period. Experiments designed to investigate particulate water column (re)cycling revealed limited iron remineralisation from freshly produced upper ocean particles. The main pathway of iron transfer from particulates into the dissolved phase was through rapid (<2 d) release of extra-cellular adsorbed iron, which, if occurring in situ, could contribute to observed higher sub-surface dissolved Fe concentrations. This was accompanied by a small loss of cellular carbon, likely through respiration of the fixed 14 C, and limited dissolution of particulate 32 Si to dissolved 32 Si. Decoupling of the remineralisation length scales for Fe, C and Si, with Fe having the fastest turnover, is thus likely in the upper mesopelagic zone beneath the bloom. Highlights: Sinking diatom cells are viable in the upper mesopelagic, resisting remineralisation by microbial degradation. Abiotic release of extracellular Fe, retention of bSiO2 and respiration of C decouples the remineralisation length scales. Abiotic release of extracellular Fe could be taken up to replenish cellular Fe or mixed to the surface to prolong a bloom.